Modeling of stress-strain state of piping systems with erosion and corrosion wear - Doroshenko, Ya. V.; Oliinyk, A. P.; Karpash, O. M. (Physics and Chemistry of Solid State, 2020)
The problems of modeling the stress-deformed state of erosion or corrosion-worn rectilinear sections and the ball-shaped bends of pipeline systems are proposed to solve in a cylindrical coordinate system. For this purpose, formulas of Christophell type II, non-zero components of the strain tensor and a system of equilibrium equations in the framework of linear torsional theory are given. The system of equilibrium equations is reduced to one equation, which is the basic equation of the Lame’s problem. Formulas for the calculation of ring stresses that occur in the wall of erosion or corrosion worn rectilinear sections, and the removal of pipelines from the action of internal pressure are derived. The influence of the change in the wall thickness of the pipeline bends in the place of their erosion or corrosion wear on the amount of ring stresses is determined.